Peningkatan Pemahaman Parenting Berbasis Ekoteologi Bagi Terwujudnya Ibu Bahagia dalam Perspektif Hadis Nabi - Abdullah Fatich; Aniqoh Aniqoh; Nur Jannah; Abdul Aziz (Institut Agama Islam Syubbanul Wathon Magelang, 2026)
This community service program aims to enhance mothers’ understanding of eco-theological parenting based on the Prophet’s Hadiths as an effort to create happy mothers and environmentally conscious families. The main problems addressed include mothers’ limited understanding of the connection between parental roles, the teachings of the Hadith, and their responsibility as khalifah in caring for nature; the high psychological and social burdens faced by mothers; and the lack of a mentoring model that translates local religious traditions into concrete, eco-friendly parenting practices. The program activities include eco-theological parenting training classes, the development of an eco-theological parenting for happy mothers module, community-based practices at the neighborhood level (such as waste donation, family gardens, and green-clean home initiatives), and strengthening collaborations with religious leaders to incorporate environmental Hadith themes into women’s study groups. The expected outcomes are improved knowledge and awareness among mothers regarding environmental Hadiths, the formation of parenting patterns that integrate spirituality, ecological awareness, and maternal well-being, as well as the development of a village-based eco-theological parenting model that can be replicated in other contexts.